Bioactive plant waste components targeting oral bacterial pathogens as a promising strategy for biofilm eradication - Mashal, Saima; Siddiqua, Aisha; Ullah, Niamat; Baloch, Rabia; Khan, Momin; Hasnain, Syed Zia Ul; Imran Aziz, Muhammad; Huseynov, Elchin; Selakovic, Dragica; Rosic, Gvozden; Makhkamov, Trobjon; Yuldashev, Akramjon; et al. (Frontiers in Chemistry, 2024)
The significance of this study lies in its exploration of bioactive plant extracts as a promising avenue for combating oral bacterial pathogens, offering a novel strategy for biofilm eradication that could potentially revolutionize oral health treatments. Oral bacterial infections are common in diabetic patients, however due to development of resistance treatment options are limited. Keeping in mind excellent antimicrobial properties of phenolic compounds, we investigated them against isolated oral pathogens using in silico and in vitro models. We performed antibiogram studies, minimum inhibitory concentration (MIC), antibiofilm and antiquorum sensing activities covering phenolic compounds. Bacterial strains were isolated from female diabetic patients and identified by using16s rRNA as Pseudomonas aeruginosa, Bacillus chungangensis, Bacillus paramycoides, Bacillus chungangensis and Paenibacillus dendritiformis. Antibiograms studies confirmed that all strains were resistant to most of tested antibiotics except imipenem and ciprofloxacin. Molecular docking analysis revealed significant interaction of rutin, quercetin, gallic acid and catechin with transcription regulator genes 1RO5, 4B2O and 5OE3. All tested molecules followed drug likeness rules except rutin.MIC values of tested compounds varied from 0.0625 to 0.5 mg/mL against clinical isolates. A significant antibiofilm activity was recorded in case of catechin (73.5±1.6% inhibition against Bacillus paramycoides) cinnamic acid (80.9±1.1% inhibition against Pseudomonas aeruginosa), vanillic and acid quercetin (65.5±1.7% and 87.4±1.4% inhibition against Bacillus chungangensis) at 0.25-0.125 mg/mL. None of the phenolic compounds presented antiquorum sensing activity. It was therefore concluded that polyphenolic compounds may have potential to be used against oral bacterial biofilms and further detailed mechanistic investigations can be performed.